Adenylate Kinase 4 Promotes Inflammatory Gene Expression via Hif1α and AMPK in Macrophages - Chin, Wei-Yao; He, Chi-Ying; Chow, Tsun Wai; Yu, Qi-You; Lai, Liang-Chuan; Miaw, Shi-Chuen (Frontiers in Immunology, 2021)
Macrophages comprise the front line of defense against various pathogens. Classically activated macrophages (M1), induced by IFN- and LPS, highly express inflammatory cytokines and contribute to inflammatory processes. By contrast, alternatively activated macrophages (M2) are induced by IL-4 and IL-13, produce IL-10, and display anti-inflammatory activity. Adenylate kinase 4 (Αk4), an enzyme that transfers phosphate group among ATP/GTP, AMP and ADP, is a key modulator of ATP and maintains the homeostasis of cellular nucleotides which is essential for cell functions. However, its role in regulating the function of macrophages is not fully understood. Here we report that Ak4 expression is induced in M1 but not M2 macrophages. Suppressing the expression of Ak4 in M1 macrophages with shRNA or siRNA enhances ATP production and decreases ROS production, bactericidal ability and glycolysis in M1 cells. Moreover, Ak4 regulates the expression of inflammation genes, including Il1b, Il6, Tnfa, Nos2, Nox2 and Hif1a, in M1 macrophages. We further demonstrate that Ak4 inhibits the activation of AMPK and forms a positive feedback loop with Hif1 to promote the expression of inflammation-related genes in M1 cells. Furthermore, RNA-seq analysis demonstrates that Ak4 also regulates other biological processes in addition to the expression of inflammation-related genes in M1 cells. Interestingly, Ak4 does not regulate M1/M2 polarization. Taken together, our study uncovers a potential mechanism linking energy consumption and inflammation in macrophages.